Prisons and punishment in America: examining the facts - O'Hear, Michael (Contemporary debates, 2018)
American sentencing : law and practice -- Alternatives to incarceration -- The experience and consequences of incarceration -- Release and life after prison -- Women, juveniles, and other special offender populations -- Causes and significance of "mass incarceration" -- Race, ethnicity, and punishment -- Public opinion, politics, and reform -- Index -- About the author